Miniestaquia, enxertia e alporquia de Khaya anthotheca - Barbosa Filho, Joamir (2015)
Khaya anthotheca A. Juss. (Welw.) is a species of african mahogany that rises in brazilian scene as a promising alternative for forestation with species of hardwood. However, the high cost of its seeds and its short period of viability are some factors that hinder the provision seedlings in the market at affordable prices. The aim this research was to evaluate the efficiency of minicutting technique, grafting and air layering to establish an clonal propagation method for Khaya anthotheca. In the first experiment of minicutting, ministumps were treated with the following fertigation solutions: S100 - 100% of nutrient concentration (control solution), S50 - 50% of nutrient concentration and S25 - 25% of nutrient concentration. The experimental design was randomized complete block in a factorial arrangement (3x5) with split-plot in the time. The factors consisted of 3 fertirrigation solutions (S100, S50 and S25) and 5 propagules collection. Ministump survival and minicutting production were evaluated. In the second stage of the experiment, minicuttings were submitted to different nutrient solutions and part of them been treated with Indol-3-butyric acid - IBA (2 g.L-1) and other part was not treated with IBA (control). The experimental design was completely randomized in a factorial arrangement (3x5x2) with split-plot in time. The factors consisting of 3 fertirrigation solutions (S100, S50 and S25), 5 propagules collection and two IBA concentrations (A0 - without AIB, A2 - 2 g.L-1 IBA). Minicutting survival in greenhouse (SCV); minicutting survival in shade-house (SCS), adventitious rooting in full sun area (EAPS) and presence of callus (CAL) were evaluated. In the grafting, combinations of Khaya anthotheca and Swietenia macrophylla King. were tested (rootstock + graft): TSK - Swietenia macrophylla + Khaya anthotheca; TKS - Khaya anthotheca + Swietenia macrophylla; TSS - Swietenia macrophylla + Swietenia macrophylla; TKK - Khaya anthotheca + Khaya anthotheca. The experimental design was randomized complete block, with the treatments constituted by 4 grafting combination. The survival was evaluated at 45 and 200 days after the grafting, followed by histological analysis. The fourth experiment was performed air layering in seedlings of Khaya anthotheca. Seedlings were fertigated with solutions of S100, S50 and S25, and after 45 days, was performed air layering with application of three IBA concentrations (A0 - without IBA, control; A3 - 3 g.L-1 IBA and A8 - 8 g.L-1 AIB). The experimental design was randomized complete block in a factorial arrangement (3x3). The factors consist of 3 fertigation solutions and 3 IBA concentrations. Survival of ministumps did not vary significantly, regardless of shoots collection and nutrient solution. The S100 solution resulted in higher values of minicuttings production per square meter per year. The minicutting survival in the greenhouse was high, regardless of the shoots collection, nutrient solution and IBA application. The minicuttings survival in shade house and rooting in full sun area were xiv higher when treated with S100 and S50 solutions and application of 2 g.L-1 de IBA. The S25 solution in the IBA absence resulted in low rooting index and greater callogenesis index. In grafting, the best survival (45 and 200 days) was the TKK combination (92%), followed by the TSK (52%) and TSS (48%). There wasn’t survival in grafting of TKS, indicating incompatibility. For air layering, the seedlings treated with S100 and S50 solutions and AIB application (3 g.L-1 and 8 g.L-1) showed the highest adventitious rooting percentage. The S25 solution without IBA application increased the callus formation and low adventitious rooting. The three propagation techniques (i.e., minicutting, grafting and air layering) were suitable for multiplication of Khaya anthotheca, demonstrating feasibility for the clone production.